A concepção de ferramentas de tradução como dinamizadoras da produção tradutória e seus reflexos para a prática - Stupiello, Erika Nogueira de Andrade [UNESP] (2011)
Transformations in the globalized world have promoted the growth in the production of information and the urgency of its dissemination beyond borders. Such fact has led to the significant increase in the demand for translations delivered at short turnarounds and according to specific production standards. In order to meet such demand, the application of technological tools is increasingly more common, such as machine translation programs and translation memory systems. This paper analysis the theoretical conceptions implicit in the projects of these tools and discusses how the automation of the translation activity directly interferes with the determination of the final responsibility for the translation.